The relationship between exchange rates and international trade: A literature review - Marc Auboin; Michele Ruta (Center for Economic Studies and ifo Institute (CESifo), 2012)
This paper surveys a wide body of economic literature on the relationship between currencies and trade. Specifically, two main issues are investigated: the impact on international trade of exchange rate volatility and of currency misalignments. On average, exchange rate volatility has a negative (even if not large) impact on trade flows. The extent of this effect depends on a number of factors, including the existence of hedging instruments, the structure of production (e.g. the prevalence of small firms), and the degree of economic integration across countries. The second issue involves exchange rate misalignments, which are predicted to have short-run effects in models with price rigidities. However, the exact impact depends on a number of features, such as the pricing strategy of firms engaging in international trade and the importance of global production networks. This effect is predicted to disappear in the long-run, unless some other distortion characterizes the economy. Empirical results confirm that short-run effects can exist, but their size and persistence over time are not consistent across different studies.
Keywords: F10; F31; F55; 330; exchange rates; volatility; misalignments; international trade flows; Wechselkurs; Außenwirtschaft; Volatilität